Modelling the potential for soil carbon sequestration using biochar from sugarcane residues in Brazil - Lefebvre, David; Williams, Adrian; Meersmans, Jeroen; Kirk, Guy J. D.; Sohi, Saran; Goglio, Pietro; Smith, Pete (Nature Publishing Group / Nature Research / Springer Nature, 2020)
Sugarcane (Saccharum officinarum L.) cultivation leaves behind around 20 t ha−1 of biomass residue after harvest and processing. We investigated the potential for sequestering carbon (C) in soil with these residues by partially converting them into biochar (recalcitrant carbon-rich material). First, we modified the RothC model to allow changes in soil C arising from additions of sugarcane-derived biochar. Second, we evaluated the modified model against published field data, and found satisfactory agreement between observed and predicted soil C accumulation. Third, we used the model to explore the potential for soil C sequestration with sugarcane biochar in São Paulo State, Brazil. The results show a potential increase in soil C stocks by 2.35 ± 0.4 t C ha−1 year−1 in sugarcane fields across the State at application rates of 4.2 t biochar ha−1 year−1. Scaling to the total sugarcane area of the State, this would be 50 Mt of CO2 equivalent year−1, which is 31% of the CO2 equivalent emissions attributed to the State in 2016. Future research should (a) further validate the model with field experiments; (b) make a full life cycle assessment of the potential for greenhouse gas mitigation, including additional effects of biochar applications on greenhouse gas balances.